Safety of the breast‐feeding infant after maternal anesthesia. Issue 4 (24th December 2013) - Dalal, Priti G.; Bosak, Jodi; Berlin, Cheston; Bosenberg, Adrian
Summary There has been an increase in breast‐feeding supported by the recommendations of the American Academy of Pediatrics and the World Health Organization. An anesthesiologist may be presented with a well‐motivated breast‐feeding mother who wishes to breast‐feed her infant in the perioperative period. Administration of anesthesia entails acute administration of drugs with potential for sedation and respiratory effects on the nursing infant. The short‐term use of these drugs minimizes the possibility of these effects. The aim should be to minimize the use of narcotics and benzodiazepines, use shorter acting agents, use regional anesthesia where possible and avoid agents with active metabolites. Frequent clinical assessments of the nursing infant are important. Available literature does suggest that although the currently available anesthetic and analgesic drugs are transferred in the breast milk, the amounts transferred are almost always clinically insignificant and pose little or no risk to the nursing infant.